Perencanaan dan Pengendalian Produksi Susu dengan Metode Economic Production Quantity (EPQ) Multi item - Ajat Lasmana; M. Yusuf Fajar; Gani Gunawan (Bandung Conference Series: Mathematics, 2022)
Abstract. In the company there is still a problem of excess inventory to be distributed. Excess or shortage of inventory is a factor that triggers an increase in costs. The amount of inventory that is too much will result in waste in storage costs, but if the amount of inventory is less it will result in the loss of the company's opportunity to make a profit. Therefore, the company must plan and optimize the amount of production with a minimum total inventory cost. The solution that can be done to answer these problems is an improvement in the production control system. This improvement can be done through the calculation of production control using the multi item Economic Production Quantity (EPQ) method. Economic Production Quantity (EPQ) is an inventory model where the product is made by the company itself. The purpose of the Economic Production Quantity (EPQ) model is to determine the optimal amount of production to minimize total inventory costs. This research was conducted at PT. IS with 130 ml milk products with apple, orange and strawberry flavors and 70 ml strawberry and orange milk. The results of the calculation using the multi-item EPQ method, obtained the optimal milk production quantity as much as 14,835.7 milk cartons 130 ml apples, 17,295.6 milk cartons 130 ml oranges, 17,943.2 milk cartons 130 ml strawberries, 10,192 milk cartons 70 ml strawberries and 9,954 ,3 cartons of 70 ml orange milk with a minimum total inventory cost of Rp. 4,921,709,700. Keywords : Economic Production Quantity (EPQ), Total Cost, Inventory. Abstrak. Didalam perusahaan masih terjadi permasalahan kelebihan jumlah persediaan yang akan disalurkan. Kelebihan atau kekurangan persediaan merupakan faktor yang memicu peningkatan biaya. Jumlah persediaan yang terlalu banyak akan berakibat pemborosan dalam biaya simpan, tetapi apabila jumlah persediaan kurang maka akan mengakibatkan hilangnya kesempatan perusahaan untuk mendapatkan keuntungan. Oleh karena itu, perusahaan harus merencanakan dan mengoptimalkan jumlah produksi dengan total biaya persediaan yang minimum. Solusi yang dapat dilakukan untuk menjawab persoalan tersebut maka diperlukan suatu perbaikan sistem pengendalian produksi. Perbaikan ini dapat dilakukan melalui perhitungan pengendalian produksi dengan menggunakan metode Economic Production Quantity (EPQ) multi item. Model Economic Production Quantity (EPQ) merupakan sebuah model persediaan yang mana produknya dibuat sendiri oleh perusahaan. Tujuan dari model Economic Production Quantity (EPQ) untuk menentukan besarnya jumlah produksi yang optimal untuk meminimumkan total biaya persediaan. Penelitian ini dilakukan di PT. IS dengan produk Susu 130 ml varian rasa apel, jeruk dan storberi serta Susu 70 ml varian stroberi dan jeruk. Hasil perhitungan dengan menggunakan metode EPQ multi item, memperoleh kuantitas produksi susu optimal sebanyak 14.835,7 karton susu 130 ml apel, 17.295,6 karton susu 130 ml jeruk, 17.943,2 karton susu 130 ml stroberi, 10.192 karton susu 70 ml stroberi dan 9.954,3 karton susu 70 ml jeruk dengan total biaya persediaan minimum sebesar Rp. 4.921.709.700. Kata Kunci: Economic Production Quantity (EPQ), Total Cost, Persediaan.